2018
DOI: 10.3389/fchem.2018.00619
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Drug Delivery: Where the Field Is Going

Abstract: Targeted delivery of anticancer drugs is considered to be one of the pillars of cancer treatment as it could allow for a better treatment efficiency and less adverse effects. A promising drug delivery approach is magnetic drug targeting which can be realized if a drug delivery vehicle possesses a strong magnetic moment. Here, we discuss different types of magnetic nanomaterials which can be used as magnetic drug delivery vehicles, approaches to magnetic targeted delivery as well as promising strategies for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
132
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 243 publications
(140 citation statements)
references
References 68 publications
0
132
0
Order By: Relevance
“…Another very popular drug-delivery system is magnetic drug targeting which involves the use of a drug delivery vehicle with magnetism properties that can be manipulated by an EMF. Both these strategies decrease the side effects caused by antineoplastic systemic treatment [6]. Most of the MNPs used in biomedical applications are the so-called SPIONs consisting of one or multiple magnetite or maghemite cores and with biocompatible shell functionalized with various modifiers.…”
Section: Drug Deliverymentioning
confidence: 99%
See 3 more Smart Citations
“…Another very popular drug-delivery system is magnetic drug targeting which involves the use of a drug delivery vehicle with magnetism properties that can be manipulated by an EMF. Both these strategies decrease the side effects caused by antineoplastic systemic treatment [6]. Most of the MNPs used in biomedical applications are the so-called SPIONs consisting of one or multiple magnetite or maghemite cores and with biocompatible shell functionalized with various modifiers.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Even though the concept of magnetic drug delivery was used for the first time in the 1980s [6], and the first clinical cancer therapy trials in humans using magnetic microspheres filled with 4-epidoxorubcin was reported in Germany in the 1990s (being about the treatment of advanced solid liver cancer in 14 patients) [84], the development of the domain has been achieved especially in the last 10 years after the development of stronger magnets and sophisticated magnetic probes, namely the theranostic probes that allow the combination of diagnostic and treatment. In this case, the diagnostic could be achieved through MRI or magnetic particle imaging, while the therapy could be realized by approaches such as hyperthermia, drug release or magneto-drug delivery [6].…”
Section: Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…A promising application of magnetic NPs is as drug carriers for so‐called magnetic drug delivery . The idea is to conjugate magnetic NPs to the drug molecules or to fill NP shells with a drug in order to guide them to a chosen site under an applied magnetic field . These delivery vehicles can be held at a desired location until the therapy is finished and then finally removed by turning the magnetic field off.…”
Section: Introductionmentioning
confidence: 99%